TO INSPIRE YOUNG GENERATION TO PLAY FOOTBALL - Komilov Jamoliddin Karimjonovich (Scholar Express Journal, 2022)
Sport is a universal tool that helps to feel great both physically and mentally. Sport is especially useful for children. When playing sports, the child develops physical abilities and, in addition, makes new friends, learns to be part of the team, learns the principles of fair play, values himself and enjoys. By increasing sports fans in our country and involving them especially in football, it also helps them to follow a healthy lifestyle. In this article, feedback and feedback will be made about the interest of young children in football.
Keywords: young generations; football; inspiration; engagement